Effectively Of 17α-Methyltestosterone on Tropical Eel, Anguilla bicolor McClelland Masculinization in Different Salinity Culture - Farida Nur Rachmawati; Ridwan Affandi; Yulia Sistina (Journal Omni-Akuatika)
Eel population in nature reaches critical number, so that culture strategy is urgently needed to fulfil the high demand of this fish. A shortcut to get functional male, which proven difficult to be founded from natural catching, is masculinization. This research aimed to induce masculinization of tropical eel, Anguilla bicolor McClelland supplemented with various doses of 17α-methyltestosterone during a month culture in freshwater (0 ppt) or brackish water (10 ppt).  The eel was grouped and fed with supplementation of 17α-methyltestosterone at various doses, depending upon treatments, namely 0 mg Kg-1 diet (control), 40, 80 or 120 mg Kg-1 diet. Eels size were similar, at approximately 16,78 g ± 0,62 in weight and 25,38 cm ± 0,15 in length were either culture in freshwater or brackish during the experiment for eight weeks. Sex gonad, based on anatomical histological structures, Eye Index and Fin Index were measured after time culture treatment achieved, as well as body length, weight, eye diameter and the length of the pectoral fin were measured. Results showed that supplementation 17α-methyltestosterone 80 mg/Kg diet culture in brackish water has the highest number of male (90%).  This study proven that, the hormone was effective for masculinization in eels, It useful for masculinization in eels. Results proved that the 17α-methyltestosterone highly significant (P<0.01) effect on the Eye index (3.63 – 5.14) and Fin Index (3.03 – 4.08) of eels. This study concluded, that 17α-methyltestosterone more effective in improving the number of males in brackish water than in freshwater culture.